Gastric carcinoma and acute myeloid leukemia: A case report of a double malignancy - Supriya Pradhan; Mingma Sherpa (Wolters Kluwer Medknow Publications, 2018)
A double malignancy involving a solid organ and hematopoieteic system is rare. We report an interesting case of gastric adenocarcinoma with subsequent development of acute myeloid leukemia, in the absence of any therapeutic intervention.